Compartments in medulloblastoma with extensive nodularity are connected through differentiation along the granular precursor lineage - Ghasemi, David R.; Okonechnikov, Konstantin; Rademacher, Anne; Tirier, Stephan Marius; Maaß, Kendra K.; Schumacher, Hanna; Joshi, Piyush; Gold, Maxwell P.; Sundheimer, Julia; Statz, Britta; Rifaioglu, Ahmet; Bauer, Katharina; et al. (Nature Communications, 2024)
Medulloblastomas with extensive nodularity are cerebellar tumors characterized by two distinct compartments and variable disease progression. The mechanisms governing the balance between proliferation and differentiation in MBEN remain poorly understood. Here, we employ a multi-modal single cell transcriptome analysis to dissect this process. In the internodular compartment, we identify proliferating cerebellar granular neuronal precursor-like malignant cells, along with stromal, vascular, and immune cells. In contrast, the nodular compartment comprises postmitotic, neuronally differentiated malignant cells. Both compartments are connected through an intermediate cell stage resembling actively migrating CGNPs. Notably, we also discover astrocytic-like malignant cells, found in proximity to migrating and differentiated cells at the transition zone between the two compartments. Our study sheds light on the spatial tissue organization and its link to the developmental trajectory, resulting in a more benign tumor phenotype. This integrative approach holds promise to explore intercompartmental interactions in other cancers with varying histology.
Gesehen am 13.02.2024